Cadeia produtiva da farinha de mandioca na perspectiva da análise de filière e supply chain management :um estudo de caso das relações entre a agroindústria e a distribuição - Ferreira, Nildete Maria da Costa (2006)
This research aims to study the manioc flour productive chain in order to understand how the relationship between its segments happens, specially between the flour agroindustry and the distribuition. This research was made from a study of case that envolved three agro industries from the Potiguar wasteland and a company of food distribution. The filiére and the supply chain management analysis were applied to identify the functioning and the organization of the manioc flour productive chain. From the study of case it s noticed that the existing contracts, even the informal ones, has mutual benefits and it suggests that they be legalized